2021
DOI: 10.3389/fmolb.2021.655126
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the TRIM58 Gene by Aberrant Promoter Methylation is Associated with a Poor Patient Outcome and Promotes Cell Proliferation and Migration in Clear Cell Renal Cell Carcinoma

Abstract: To investigate the underlying molecular mechanism of tripartite motif-containing 58 (TRIM58) in the development of clear cell renal cell carcinoma (ccRCC), we explored TRIM58 expression and methylation in tumor tissues and the association with clinicopathological features and prognosis of tissue samples; Moreover, we examined the direct gene transcription of TRIM58-specific DNA demethyltransferase (TRIM58-TET1) by the CRISPR-dCas9 fused with the catalytic domain of TET1 and the biological functions in RCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…phagocytosis (e.g., VAV3, NCF2, C4BPA, DYSF, MARCO, CD302 ), regulation of innate immune response (e.g., GBP2, ADAR, FCRL3, IFI16, AIM2, CFH ), and interleukin-1 beta production (e.g., IFI16, AIM2, NLRC4, CASP8, GHRL, CX3CR1 ), highlighting the impact of splicing on immune-related genes (Supplementary Figure 3, Table S6). Indeed, some of the strongest sQTL signals are present in immune-related genes such as TRIM58, which is additionally implicated in malignancies such as lung cancer, liver cancer, and pancreatic ductal adenocarcinoma [69][70][71][72], and is involved in innate immunity and cell proliferation [69,73], and ERMAP, which is a B7 family immune regulator that has been found…”
Section: Characterisation Of Indonesian Cis-sqtls In Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…phagocytosis (e.g., VAV3, NCF2, C4BPA, DYSF, MARCO, CD302 ), regulation of innate immune response (e.g., GBP2, ADAR, FCRL3, IFI16, AIM2, CFH ), and interleukin-1 beta production (e.g., IFI16, AIM2, NLRC4, CASP8, GHRL, CX3CR1 ), highlighting the impact of splicing on immune-related genes (Supplementary Figure 3, Table S6). Indeed, some of the strongest sQTL signals are present in immune-related genes such as TRIM58, which is additionally implicated in malignancies such as lung cancer, liver cancer, and pancreatic ductal adenocarcinoma [69][70][71][72], and is involved in innate immunity and cell proliferation [69,73], and ERMAP, which is a B7 family immune regulator that has been found…”
Section: Characterisation Of Indonesian Cis-sqtls In Whole Bloodmentioning
confidence: 99%
“…This observation is consistent with previous research suggesting that most variants that fall in close proximity to splice junctions influence splicing regulatory functions [67,68] GO enrichment analysis of sGenes (genes with a significant sQTL) revealed enrichment for numerous immune-related pathways, including: immune response-regulating signaling (e.g., THEMIS2, ERMAP, GBP2, VAV3, FCRL3, AIM2, FCGR3A), immune response-activating signaling (e.g., DENND1B, MAPKAPK2, CR1, NLRC4, NAGK, IFIH1, PRKCD), phagocytosis (e.g., VAV3, NCF2, C4BPA, DYSF, MARCO, CD302 ), regulation of innate immune response (e.g., GBP2, ADAR, FCRL3, IFI16, AIM2, CFH ), and interleukin-1 beta production (e.g., IFI16, AIM2, NLRC4, CASP8, GHRL, CX3CR1 ), highlighting the impact of splicing on immune-related genes (Supplementary Figure 3, Table S6). Indeed, some of the strongest sQTL signals are present in immune-related genes such as TRIM58, which is additionally implicated in malignancies such as lung cancer, liver cancer, and pancreatic ductal adenocarcinoma [69][70][71][72], and is involved in innate immunity and cell proliferation [69,73], and ERMAP, which is a B7 family immune regulator that has been found to promote the phagocytosis of tumor cells [74][75][76] and encodes the protein responsible for the Scianna blood group system [77] (Supplementary Figure 4).…”
Section: Characterisation Of Indonesian Cis-sqtls In Whole Bloodmentioning
confidence: 99%
“…The tripartite-motif (TRIM) family proteins contribute to cancer initiation, progress, or therapy resistance, exhibiting tumor-suppressive functions: they are frequently downregulated by promoter methylation in cancerous tissues [155]. dCas9-TET1CD induced specific demethylation of TRIM58 in renal carcinoma cells (RCC) [156]. Promoter of the TMEM244 gene was demethylated to upregulate its expression in Sézary syndrome-an aggressive form of cutaneous T-cell lymphoma [157].…”
Section: Selection Of Demethylase For Targeted Dna Demethylationmentioning
confidence: 99%
“…17 Previous studies reported that TRIM58 served as tumor suppressor and conferred better survival in gastric cancer, thyroid cancer, colorectal cancer and renal cell carcinoma. [18][19][20][21] Our previous study identified that TRIM58 was highly expressed in drug-resistant breast-cancer cell strains and inactivated p53/p21 to promote chemoresistance by ubiquitination of DEAD-Box Helicase 3 X-Linked (DDX3) in breast cancer. 22 However, it remains unclear whether TRIM58 expression levels influence the individual clinical benefits of NAT.…”
Section: Introductionmentioning
confidence: 99%